2018
DOI: 10.1183/20734735.000318
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in respiratory function

Abstract: Men Are from Mars, Women Are from Venus. John Gray used this provocative title for his book to describe the fundamental psychological differences between the sexes. Many other controlled studies and brain scans demonstrate that men and women are physically and mentally different. The purpose of this physiology masterclass is to illustrate how sex-related differences are present in respiratory function and their possible clinical implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
185
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(199 citation statements)
references
References 70 publications
11
185
0
3
Order By: Relevance
“…However, this result should be interpreted with caution, since the relationship is likely to be influenced by confounding variables (eg, sex, body height). Specifically, females show lower VE max values and female's lung function affects the response to exercise due to stature . In our study, we can confirm FVC was also related to VE max , where between 6 and 20 minutes post‐exercise, FVC reductions in the HME condition were negatively correlated with VE max .…”
Section: Discussionsupporting
confidence: 63%
“…However, this result should be interpreted with caution, since the relationship is likely to be influenced by confounding variables (eg, sex, body height). Specifically, females show lower VE max values and female's lung function affects the response to exercise due to stature . In our study, we can confirm FVC was also related to VE max , where between 6 and 20 minutes post‐exercise, FVC reductions in the HME condition were negatively correlated with VE max .…”
Section: Discussionsupporting
confidence: 63%
“…Sexual dimorphism is an important factor underlying morphological variation in the entire human body, including the respiratory system (Frayer & Wolpoff, ; Franciscus, ; Krishtalka et al, ; Lam et al, ; Lockwood, ; Lockwood et al, ; LoMauro and Aliberti, ; McHenry, ; Molgan‐Seon et al, ; Plavcan, , , , ; Ponce de León et al, ; Rehg & Leigh, ; Reno et al, ; Reno et al, ; Richmond & Jungers, ; Wood, ; Bastir et al, ; Hall, ; Holton et al, ; Rosas & Bastir, , ; Rosas et al, ; Bastir et al, ; Carlson et al, ; Fischer & Mitteroecker, , ; İşcan & Shihai, ; Kranioti et al, ; García‐Martínez et al, ; Mitteroecker & Fischer, ; Rascón Pérez, ; Rosas et al, , ; Walker, ; Walker, ; Weinstein, ). García‐Martínez et al () quantified static thoracic morphology and found that males have more horizontally oriented ribs than females, as well as relatively shorter and wider ribcages, particularly in the caudal part.…”
Section: Resultsmentioning
confidence: 99%
“…This period is also significant for the development of lung function as it represents a phase of dramatic growth from childhood to adolescence to reach a maximal level of lung function in early adulthood [3][4][5]. Lung function growth is genderdependent and such dependence is attributable to multiple biological determinants, including dimensional/ anatomical (e.g., airway size, somatic growth, lung growth, adolescence growth spurts), immunological, and hormonal determinants such as different phases of the menstrual cycle and common hormonal and metabolic conditions [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%